Business Model of Indonesian Fintech Crowdfunding - Aqmalia, Wima Rizky; Dadan Rahadian; Astrie Krisnawati (Indonesian Journal of Business Analytics, 2024)
Fintech crowdfunding has emerged as one of the most widely used for entrepreneurs which starts their businesses. However, fintech crowdfunding isn't growing in the same way as other fintech, thus the business model and strength are yet unidentified. This study's purpose is to identify and analyze the fintech crowdfunding business model alongside its strengths. This study method takes a qualitative approach. The data was processed using NVIVO 14. This study focuses on fintech crowdfunding licensed by the Financial Services Authority. The study results show that the fintech crowdfunding business model concept is network-centric and emphasizes the value exchange between all of the model elements. The value proposition and key activity are the aspects that make fintech equity crowdfunding effective.